E-Learning Implementation: Infrastructure Support, Human Resource Training, and Effective Learning Strategies - Dwi Rahma Tika (Konsultan Jurnal Ilmiah Indonesia, 2025)
The purpose of this study is to determine the effectiveness of infrastructure support, human resource training, and learning strategies. The method used in this article is qualitative library research, which utilizes primary and secondary sources, including books, scientific journal articles, and other sources discussing infrastructure support, human resource training, and effective learning strategies. The findings of this study demonstrate the use of e-learning to increase competitiveness through strategic steps. The development of a localized LMS tailored to the needs of students and lecturers is a priority. Furthermore, intensive training for lecturers, collaboration with industry, and the development of locally based content can strengthen e-learning implementation.